Statistics of Financial Markets An Introduction - Franke, Jürgen; Härdle, Wolfgang Karl; Hafner, Christian Matthias (Universitext,, 2011)
Statistics of Financial Markets offers a vivid yet concise introduction to the growing field of statistical application in finance. The reader will learn the basic methods of evaluating option contracts, analysing financial time series, selecting portfolios and managing risks making realistic assumptions of the market behaviour. The focus is both on the fundamentals of mathematical finance and financial time series analysis and on applications to given problems of financial markets, thus making the book the ideal basis for lecturers, seminars and crash courses on the topic. For the third edition the book has been updated and extensively revised. Several new aspects have been included: new chapters on long memory models, copulae and CDO valuation. Practical exercises have been added, the solutions of which are provided in the book by S. Borak, W. Härdle and B. Lopez Cabrera (2010) ISBN 978-3-642-11133-4. "Both R and Matlab Code, together with the data, can be downloaded by clicking on the Additional Information tab labeled "R and Matlab Code," which you will find on the right-hand side of the webpage.".